HEAVY AND LIGHT BODY PARTS: THE WEIGHING METAPHOR IN EARLY CHINESE DIALOGUES*. (15th May 2015) - Defoort, Carine
Abstract: The article analyses the metaphorical use of weighing body parts such as fingers, arms, or a head. Our understanding of the weighing metaphor has been much influenced by A. C. Graham's characterization of its rhetorical mechanism, followed by Griet Vankeerberghen in her description of one type of weighing ( quan B). The basis of this understanding are two corrupt textual fragments in the dialectical chapters of the Mozi . Several Lü shi chunqiu chapters, however, contain a set of argumentative stories in which body parts are weighed in terms of light and heavy. These stories always argue in favor of life and health, they have a relatively consistent structure, and they may have constituted the core of a larger set of related arguments. Insight into their working can therefore enlighten our reading of other texts. 提要: 本文分析古籍中權衡身體部位(如指、臂、頭)的隱喻。當前對這個議題的認識主要是來自葛瑞漢 (A. C. Graham) 對於此隱喻的修辭功能的分析，以及方麗特 (Griet Vankeerberghen) 對於某一類型的「權」(本文稱為「權B」)的描述。他們依據的文獻主要是墨辯裡的兩個零星片段。本文提出《呂氏春秋》中有一些關於衡量肢體輕重的故事。這類故事總是用來強調全命養生的價值，有相對一致的論述結構，並且構成一系列相關論證的核心。透過剖析這些段落，將有助於我們理解其他文本的內涵。